RETRACTION Polevoy, G. (2024). Períodos sensitivos para el desarrollo de la resistencia de los escolares (Sensitive periods for the development of endurance of schoolchildren). Retos, 55, 672–678. https://doi.org/10.47197/retos.v55.104093 - RETOS, RETOS (Retos, 2025)
Polevoy, G. (2024). Períodos sensitivos para el desarrollo de la resistencia de los escolares (Sensitive periods for the development of endurance of schoolchildren). Retos, 55, 672–678. https://doi.org/10.47197/retos.v55.104093Retraction of the article by the editor of the journal. Due to plagiarism by the author